Comprehensive Monitoring of Changes in the Geometric Structure of a Historic Building the "Sala BHP" in Gdańsk - Sztubecki, Jacek; Niedostatkiewicz, Maciej; Mrówczyńska, Maria; Majewski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents selected results of the analysis of the comprehensive monitoring of the historical building of the "Sala BHP" in Gdansk. The necessity of monitoring was caused by scratches on its structural and finishing elements that occurred in the previous period. A preliminarily assumed factor that could cause the expansion of existing damages and the possible formation of new ones was the planned implementation of an investment consisting of the erection of multi-storey buildings on adjacent plots.
Keywords: monitoring of building structures; analysis of displacements and deformations; historic building